Курдиш В. В. Алгоритм синхронізації звуку і відео в інтерв’ю - Курдиш, В. В. (ХНУРЕ, 2023)
During video editing, there is a problem of time synchronization of audio tracks recorded on a recorder with video recorded on a camera. In the Adobe Premiere program, there are several ways to synchronize sound: by input or out put tags; by time code; by markers; by surround sound. In this work, the method of time synchronization of sound tracks of voice recorders with the sound of the standard microphone of the camera is used. At the same time, the regular sound track acted as a synchronization signal. The basis of this synchronization algo rithm is the calculation of the mutual correlation function.
Keywords: синхронізація звуку і відео